The Experimental Assessment into Heavy Metal Content in Saudi Cements - Shammari, Humood L. Al (IJRDO-Journal of Applied Science, 2019)
Presence of heavy metals in cement can enhance the cement properties but can be harmful to the environment for long term due to less mobility of heavy metals. A comprehensive quantification of heavy metals contamination was carried out in the cement locally produced building materials collected from different cement factories in Riyadh city, Saudi Arabia, in which city is subject to rapid construction development. In Riyadh, it has been observed environmental issues due to heavy metal pollution from new construction projects of underground metro as well as other new infrastructural developments. Therefore, it is very important to carry out an investigation of presence of heavy metals in cement materials as major unit of construction building materials. The benefit of full statistical assessment was conducted to represent relationship models of the contents of heavy metals (Cr, Cd, Pb, Ga, and U) in cement utilized in Saudi buildings. Four different methods of matrix correlations were used to obtained full spectra of relationship between studied heavy metals and other elements. Normality tests were conducted to help the statistical performance to treat the results as parametric. Moreover, Shewhart confidence limit tests were also applied to the reported data of each heavy metals to tell us the sample out of confidence limits or not. Lucky, all the statistical tests were within good agreement with critical values. The obtained data were compared with the value of heavy metals in upper earth crust reported by Muller. Geochemical indexes calculations were performed using geochemical hazard index, background enrichment index and other useful indexes. The values of hazard indexes were compared with tabulated or recommended values. The present study was found that cement materials did not possess any significant hazard in term of heavy metals to the residents of Riyadh.